Biomechanics of marathon running - Stöggl, T.; Wunsch, T. (Marathon running: Physiology, psychology, nutrition and training aspects, 2016)
This book section starts with an introduction towards the historical development of modem marathon running with respect to number of participants, gender and age distribution and the world record marathon times. This encompasses the development of the mean running velocities, details about the applied stride characteristics (e.g. stride rate, stride length), the applied strike patterns (e.g. forefoot strike vs. heel strike), the prevalence and causes of running related injuries. The second part gives an overview about general biomechanical principles which are relevant in running. In particular, specific definitions (phase definition of the running cycle, strike patterns), force components and the mathematical basics with respect to running energetics, joint loading, leg stiffness etc. are presented. The final part gives an overview about the state of the art knowledge about performance and injury related aspects with respect to marathon running from a biomechanical perspective. Special attention is paid to anthropometries, running technique related aspects, fatigue effects and footwear.